Analisis Prosedur MRI Cervical Menggunakan MAVRIC pada Kasus Cervical Root Syndrome - Adhista Dhianida Austin; Susanto, Fani; Mastuti, Santi Tri; Ali, Azilnawati binti (Poltekkes Kemenkes Semarang, 2026)
Background: Cervical Root Syndrome (CRS) is a neurological disorder caused by compression or irritation of the cervical nerve roots. Magnetic Resonance Imaging (MRI) of the cervical spine is one of the primary modalities for evaluating CRS. In specific cases such as the presence of braces, the resulting artifacts can reduce image quality. The use of Multi-Acquisition Variable-Resonance Image Combination (MAVRIC) sequences has been introduced to minimize metal artifacts, thereby improving diagnostic accuracy. This study aims to analyze the MRI Cervical examination procedure using MAVRIC sequences in CRS patients. Methods: This research employed a qualitative method with a case study approach conducted at the Radiology Unit of Indriati Solo Baru Hospital. Data collection was carried out through direct observation, documentation, and structured interviews with radiographers. The obtained data were analyzed descriptively to understand the examination procedure and to identify its clinical implications. Results: The MRI Cervical examination in CRS patients followed the standard cervical MRI protocol, including Localizer, Coronal T2, Sagital T1, Sagital T2, Sagital T2 Fat Sat, Axial T1, Axial T2 Merge, and Myelo 2D sequences. Prior to the examination, patients underwent metal screening and removal to ensure safety and image quality. The MAVRIC sequence was added specifically to reduce metal artifacts, which enabled clearer visualization of cervical anatomical structures and pathological findings. Conclusions: The MRI Cervical examination with MAVRIC sequences provides significant benefits in reducing metal-related artifacts, thereby enhancing image quality and diagnostic accuracy in patients with Cervical Root Syndrome. Proper patient preparation and adherence to protocol are essential to maximize the effectiveness and safety of the procedure.